Process of self-representation in the writing of Afro-descendant Central American women authors: a discussion - Meza-Márquez, Consuelo (2022)
This article presents a summary of the discussion entitled: "Self-representation of Afro-Central American women in literature", held within the framework of the Meeting: Afro-descendants in the Bicentennial: ancestral practices and knowledge ", during the 23rd edition of the Festival Flores de la Diáspora Africana [Flowers of the African Diaspora]. This discussion was held between four Afro-Central American writers and has been systematized through the answer to some questions that were posed on the occasion, from which it is sought to hear from the voices of the writers themselves how they represent themselves in literature, investigating also about their literary work, their commitment as black women, to whom their literature is directed and their utopia as writers.